Development of Islamic Religious Education Learning Media Based on Comic Videos on the Leadership Material of the Prophet’s Companions for Elementary School Students - Atifah, Khusnul; Sukirman, Sukirman; Hasmuddin , Erni (South Sulawesi Education Development (SSED), 2025)
This study developed a video comic-based Islamic Religious Education learning media on the leadership material of the Prophet's Companions for grade VI students. The research method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The validation results showed a category of